Summary Surgical treatment for posterior glottic adhesion by Ejnell's technique - Hyodo, Masamitsu; Nishikubo, Kaori (JOURNAL OF JAPAN SOCIETY FOR HEAD AND NECK SURGERY, 2004)
A case of posterior glottic adhesion caused by recurrent endotracheal intubation was reported. An 81-year-old male was repeatedly intubated four times due to heart failure. Thereafter, he complained of inspiratory dyspnea. Endoscopic examination of the larynx revealed bilateral vocal cord immobility and interarytenoid adhesion. Under general anesthesia, the adhesion was cut, and the left vocal cord was laterof fixed by Ej nell's technique to prevent a recurrence of adhesion. Eighty days after the operation, the left vocal cord was released from the fixation by a cut of nylon thread. The postoperative course has been positive with a good phonatory and respiratory function 10 months after the surgery.